2019
DOI: 10.1093/ajcn/nqz036
|View full text |Cite
|
Sign up to set email alerts
|

Low circulating concentrations of citrulline and FGF19 predict chronic cholestasis and poor survival in adult patients with chronic intestinal failure: development of a Model for End-Stage Intestinal Failure (MESIF risk score)

Abstract: Background: Patients with chronic intestinal failure (CIF) often develop cholestatic liver injury, which may lead to liver failure and need for organ transplantation. Objectives: The aim of this study was to investigate whether citrulline (CIT) and the enterokine fibroblast growth factor 19 (FGF19) are associated with chronic cholestasis and survival in adult CIF patients, and to develop a risk score to predict their survival. Methods: We studied 135 adult CIF patients on intravenous supplementation (>3 mo). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Six hours after the start of the intravenous meal infusion, plasma C4 levels were still elevated compared to the overnight fasted baseline levels. This suggests that intravenous meal infusion stimulated hepatic bile acid synthesis [45]. Fxr-null mice showed increased hepatic Cyp7a1 gene expression, which reflects dis-inhibited bile acid synthesis [46].…”
Section: Discussionmentioning
confidence: 99%
“…Six hours after the start of the intravenous meal infusion, plasma C4 levels were still elevated compared to the overnight fasted baseline levels. This suggests that intravenous meal infusion stimulated hepatic bile acid synthesis [45]. Fxr-null mice showed increased hepatic Cyp7a1 gene expression, which reflects dis-inhibited bile acid synthesis [46].…”
Section: Discussionmentioning
confidence: 99%
“…Although citrulline, which is generated from glutamine by the enterocyte, reflects intestinal absorption capacity in patients with short‐bowel syndrome, altered glutamine metabolism during critical illness affects its accuracy in the intensive care unit (ICU) 17,18 . Recent work from our group has established that the bile salt–induced gut hormone fibroblast growth factor 19 (FGF19) is a prognostic marker in chronic intestinal failure and that the postprandial response of FGF19 to a lipid challenge is blunted in critically ill patients 19,20 . Preclinical studies demonstrated that FGF19 exerts several metabolic actions, including stimulation of hepatic protein synthesis and preservation of the trophic state in skeletal muscle 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Others have demonstrated resolution of chronic cholestasis following restoration of intestinal continuity of the small bowel with colon in adult patients with short bowel syndrome, possibly due to a reduction in the amount of PN administered . Disruption of the liver‐gut axis in patients with small bowel resections has also been implicated as one of the possible mechanisms contributing to the development of cholestatic IFALD in both the paediatric and adult IF populations . In the normal situation, bile salts regulate their own synthesis in the liver.…”
Section: Introductionmentioning
confidence: 99%